Analysis of Environmental Reporting Costs, Renewable Energy Adoption Costs, and Waste Minimization Costs on Environmental Performance - Widyatna, Ariyanta Dany; Mahendra Wisnu W; Suhendro Sosro JK; Samsul Arifin; Ahmad Arif; Maria Yovita R Pandin; Hwihanus (International Journal of Economics (IJEC), 2025)
This research examines the relationship between environmental reporting costs, renewable energy adoption costs, waste minimization costs, and environmental performance in Indonesian manufacturing companies. Using a quantitative methodology with multiple linear regression analysis on panel data from 45 manufacturing companies listed on the Indonesia Stock Exchange for the 2020–2024 period, this study investigates how these three environmental cost dimensions affect overall environmental performance outcomes. The regression analysis results show that environmental reporting costs (β = 0.412, p < 0.05) and waste minimization costs (β = 0.385, p < 0.05) have a statistically significant positive relationship with environmental performance, while renewable energy adoption costs (β = 0.156, p > 0.05) show a positive but insignificant relationship. The model explains approximately 78.4% of the variance in environmental performance (Adjusted R² = 0.784), with an F-statistic of 34.89 (p < 0.001), indicating that these cost variables collectively represent substantial drivers of environmental performance. This research contributes to understanding how strategic environmental investments lead to measurable environmental outcomes, particularly relevant for developing countries like Indonesia pursuing sustainable industrial development goals.